2024
DOI: 10.1002/alz.13784
|View full text |Cite
|
Sign up to set email alerts
|

The six brain‐specific TAU isoforms and their role in Alzheimer's disease and related neurodegenerative dementia syndromes

Sarah Buchholz,
Hans Zempel

Abstract: INTRODUCTIONAlternative splicing of the human MAPT gene generates six brain‐specific TAU isoforms. Imbalances in the TAU isoform ratio can lead to neurodegenerative diseases, underscoring the need for precise control over TAU isoform balance. Tauopathies, characterized by intracellular aggregates of hyperphosphorylated TAU, exhibit extensive neurodegeneration and can be classified by the TAU isoforms present in pathological accumulations.METHODSA comprehensive review of TAU and related dementia syndromes liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 453 publications
(860 reference statements)
0
1
0
Order By: Relevance
“…Due to the different accessibility of Aβ1-42 peptide regions within the fibril, we included peptide pools deriving from the linear Aβ1-42 divided into N-terminal, mid-sequence, and C-terminal pools ( Table S4 ). In addition, we included a peptide pool deriving from full-length 2N4R tau and axonal 0N4R tau variant representing both AD- and neurodegeneration-related antigens 54 . For the tau pool, we selected linear peptides showing higher predicted affinity towards HLA molecules using the NetMHCIIpan database 49,50 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the different accessibility of Aβ1-42 peptide regions within the fibril, we included peptide pools deriving from the linear Aβ1-42 divided into N-terminal, mid-sequence, and C-terminal pools ( Table S4 ). In addition, we included a peptide pool deriving from full-length 2N4R tau and axonal 0N4R tau variant representing both AD- and neurodegeneration-related antigens 54 . For the tau pool, we selected linear peptides showing higher predicted affinity towards HLA molecules using the NetMHCIIpan database 49,50 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we aimed to identify domains or motifs of Tau and cellular interaction partners that are required for efficient axonal Tau sorting. Further, we wanted to unravel isoform-specific Tau interaction partners that might support the idea of different roles of human Tau isoforms in normal function and in disease development (Buchholz & Zempel, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…The human Tau isoforms differ in their intracellular localization (Bachmann, Bell, et al, 2021; Buchholz et al, 2022; Zempel et al, 2017), and co-immunoprecipitation (Co-IP) experiments in rodent have revealed distinct binding partners suggesting isoform-specific roles in cellular Tau function (Liu et al, 2016). Comparable data are lacking for human Tau, although there is evidence for differential roles of human Tau isoforms in both health and disease (Buchholz & Zempel, 2024). Thus, we next looked for interaction partners that are specific for individual Tau isoforms, with the aim to find evidence for distinct functional roles in health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function and structure of tau are regulated by phosphorylation; however, in tauopathies including AD, FTD and DLB/PDD, tau proteins can become abnormally hyperphosphorylated. This hyperphosphorylation diminishes tau’s ability to bind to microtubules, leading to the formation of intracellular neurofibrillary tangles—one of the hallmarks neuropathologies of AD [166, 167].…”
Section: Future Directions and Limitationsmentioning
confidence: 99%